A Symbolic and Ritualistic Exposition of Purification Rites in the Old Testament - Diko, Mlamli (Journal for Semitics, 2024)
This article explores the intricate tapestry of symbolic and ritualistic elements interwoven in the purification rites of the Old Testament. Elucidating the ancient religious practises of the Israelites, this scholarly exposition unravels the profound significance and ethnological underpinnings of purification rituals as documented in sacred or biblical narratives. The Old Testament, a cornerstone of Judeo-Christian tradition, provides a rich repository of symbolic expressions and rituals designed to purify individuals and communities from impurities and sins. Through a meticulous scrutinisation of biblical references and historical context, this article unmasks the multifaceted interplay between symbolism and ritual in the Old Testament. To do this, symbolic and ritualistic theoretical frameworks are applied to the discourse. The findings and discussion show that the performative dimensions of purification rites highlight the importance of collective participation in spiritual purification, bolstering the communal responsibility for maintaining ritual purity. By navigating through the layers of symbolism and ritual, this scholarly discourse endeavours to offer a comprehensive understanding of how purification rituals serve as a profound expression of the Israelite religious philosophy, configuring their cultural identity and spiritual belief systems.